CCEA GCSE Physics - White, Roy, 1951-; McCauley, Frank (London : Hodder Education Group, 2017)
Build your students' scientific thinking and practical skills with this Third Edition textbook, developed specifically for the 2017 GCSE specifications, from the No. 1 publisher for CCEA GCSE Science. - Develop understanding with clear Examples, Tips and Practical activities. - Prepare students for assessment with Test Yourself questions, Maths practice and Exam-style questions throughout. - Provides everything you need for GCSE Physics and the Physics content of GCSE Double Award Science. - Supports Foundation and Higher-tier students in one book.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Description based on print version record.
Master record variable field(s) change: 050, 650
Keywords: Physics -- Examinations -- Study guides; Physics -- Examinations; SCIENCE / Energy; SCIENCE / Mechanics / General; SCIENCE / Physics / General; Electronic books